Functions of legal responsibility in the theory of law and state (analysis and synthesis of theoretical studies) - Volgina, A.P.; Turlayev, A.V.; Morozov, N.V. (Bulletin of the Karaganda University “Law Series”, 2021)
The article reveals different approaches to defining the functions of legal responsibility, which are given by different authors. The functions of legal responsibility are considered as a category of theory and history of law, which are detailed in sectoral legislation and expressed in legislation in the form of punishments, penalties and other forms. Different approaches and views underline the dynamism of this phenomenon. The aim of the study is to identify the main features of the functions of legal responsibility and various types of functions as directions of the legal impact of legal responsibility on public relations. With the help of general and special research methods, the analysis and generalization of theoretical material, consideration of various types of functions of legal responsibility in order to identify the patterns of development of this theoretical category are carried out. As a result of the study, we presented our own approach to understanding the functions of legal responsibility, which, in addition to the sanctions of a legal norm, also includes psychological impact aimed at correcting the behavior of a person brought to legal responsibility. The functions of legal responsibility include upbringing and education as a necessary element of the process of correcting the offender in order to more effectively influence the mind of the offender. The article draws conclusions that reveal the concept and signs of functions of legal responsibility, which are in constant development, substantiates the provision that in the category of legal responsibility, in addition to punishment, other positive and negative measures of a coercive nature should be included, provided by the coercive force of the state, directed to correct the person who committed the offense.